2018
DOI: 10.29333/ejmste/97191
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Early Numeracy Activities on Mathematics Achievement and Affect: Parental Value and Child Gender Conditions and Socioeconomic Status Mediation

Abstract: Past studies have examined the models for the effects of early numeracy activities on children's later mathematics achievement, with parental values as a precondition and socioeconomic status (SES) as an interaction measure with numeracy activities. This study proposed models of (1) the multiple effects of early numeracy activities, conditioned by parental value, on mathematics achievement and affect (e.g. confidence and interest) and (2) the multiple effects to be mediated by SES and early numeracy activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 53 publications
(84 reference statements)
2
15
0
2
Order By: Relevance
“…Similarly, Jordan et al (2010) examined the association between numeracy competencies at the beginning of kindergarten and first and third-grade mathematics achievement and found positive associations between them. Additionally, studies on Finland (Aunio & Niemivirta, 2010), Hong Kong (Zhu & Chiu, 2019), and Taiwan (Chiu, 2018) reported similar results.…”
Section: Early Numeracy Activities Early Numeracy Competencies and mentioning
confidence: 52%
See 3 more Smart Citations
“…Similarly, Jordan et al (2010) examined the association between numeracy competencies at the beginning of kindergarten and first and third-grade mathematics achievement and found positive associations between them. Additionally, studies on Finland (Aunio & Niemivirta, 2010), Hong Kong (Zhu & Chiu, 2019), and Taiwan (Chiu, 2018) reported similar results.…”
Section: Early Numeracy Activities Early Numeracy Competencies and mentioning
confidence: 52%
“…Studies have reported that early numeracy competencies acquired before starting elementary school affect students' later mathematics achievement (Aunio & Niemivirta, 2010;Chiu, 2018;Duncan et al, 2007;Galindo & Sonnenschein, 2015;Geary et al, 2018;Jordan et al, 2010;Siegler, 2016;Zhu & Chiu, 2019). Because early numeracy competencies work as the basis for acquiring new mathematical knowledge in school, students with higher schoolentry numeracy competencies tend to have higher mathematics achievement in elementary school.…”
Section: Early Numeracy Activities Early Numeracy Competencies and mentioning
confidence: 99%
See 2 more Smart Citations
“…In this article, Chiu (2018) proposed models of (i) the multiple effects of early numeracy activities, conditioned by parental value, on mathematics achievement and affect (e.g., confidence and interest) and (ii) the multiple effects to be mediated by socioeconomic status and early numeracy activities conditioned by parental value and child gender. The proposed models were examined using Structural Equation Modeling (SEM) with data from Taiwanese parental reports and child grade-4 tests and reports (N = 4,291; 49% girls) of TIMSS 2015.…”
Section: Effects Of Early Numeracy Activities On Mathematics Achievemmentioning
confidence: 99%